A step toward bio-inspired dental composites. Issue 1 (31st December 2023) - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich
Abstract: This feasibility study aimed to develop a new composite material of aligned glass flakes in a polymer resin matrix inspired by the biological composite nacre. The experimental composite was processed by an adapted method of pressing a glass flake and resin monomer system. By pressing and allowing the excess monomer to flow out, the long axis of the flakes was aligned. The resultant anisotropic composite with silanized and non-silanized glass flakes were subjected to fracture toughness tests. We observed increasing fracture toughness with increasing crack extension (Δ a ) known as resistance curve (R-curve) behavior. Silanized specimens had higher stress intensity KR -Δ a over non-silanized specimens, whereas non-silanized specimens had a much lower Young's modulus, and higher nonlinear plastic-elastic JR -Δ a R-curve. In comparison with conventional composites, flake-reinforced composites can sustain continued crack growth for more significant extensions. The primary toughening mechanism seen in flake-reinforced composites was crack deviation and crack branching. We produced an anisotropic model of glass flake-reinforced composite showing elevated toughening potential and a prominent R-curve effect. The feasibility of flake reinforcement of dental composites has been shown using a relatively efficient method. The use of a biomimetic, nacre-inspired reinforcement concept might guide further research toward improvement of dental restorative materials.